Developing Balanced Scorecard Key Performance Indicators at Sakti Garden Resort & Spa: A Case Study - Ni Putu Eka Widiantari; Ni Made Adi Erawati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study develops key performance indicators (KPIs) using the Balanced Scorecard (BSC) approach at Sakti Garden Resort & Spa, a four-star hotel located in Ubud that is currently facing competitive pressures affecting its ability to sustain and enhance performance. The Balanced Scorecard framework is applied across its four strategic perspectives: financial, customer, internal business processes, and learning and growth. A quantitative descriptive method is employed, with data collected through questionnaires, passive observation, and documentation analysis. The research process involves articulating the organization’s vision and mission, formulating strategic objectives, and subsequently identifying and measuring relevant KPIs. The study identifies ten KPIs: four within the financial perspective, one in the customer perspective, three in internal business processes, and two within the learning and growth perspective. The performance results indicate that several KPIs remain below target thresholds. Overall, the Balanced Scorecard-based KPI design offers a more integrated and strategic framework for assessing and enhancing the company's future performance.